Differential effects of antipsychotic agents on obsessive–compulsive symptoms in schizophrenia: a longitudinal study. (April 2013) - Schirmbeck, Frederike; Rausch, Franziska; Englisch, Susanne; Eifler, Sarah; Esslinger, Christine; Meyer-Lindenberg, Andreas; Zink, Mathias
Indirect evidence supports the assumption that antiserotonergic second-generation antipsychotics (SGA) induce and aggravate obsessive–compulsive symptoms (OCS) in schizophrenia. However, multimodal studies assessing the long-term interaction of pharmacotherapy and psychopathology are missing. Over 12 months, we followed-up 75 schizophrenia patients who were classified into two groups according to antipsychotic treatment: clozapine or olanzapine (group I) versus aripiprazole or amisulpride (group II). We applied the Yale Brown Obsessive Compulsive Scale (YBOCS) and investigated between-group changes over time as the primary endpoint. Group I showed markedly higher YBOCS scores at both time points. Repeated measure analyses of variance (ANOVAs) revealed significant interaction effects of group and time (per protocol sample (PP): p =0.006). This was due to persistently high OCS severity within group I, and decreasing YBOCS scores within group II. OCS severity correlated significantly with the negative and general psychopathology subscales of the Positive and Negative Syndrome Scale (PANSS), as well as with depressive symptoms. The progressive differences in OCS severity between our groups support the assumption of differential pharmacodynamic effects on comorbid OCS in schizophrenia. Further studies should address the pathogenetic mechanism, define patients at risk and facilitate early detection as well as therapeutic interventions.